Aktivitas Nitrat Reduktase Beberapa Morfologi Daun Lada yang Ditanam pada Lahan Gambut - Suswanto, Iman; Ramadhan, Tris Haris; Hernowo, Kukuh (Perkebunan dan Lahan Tropika, 2025)
Leaf organs have an important function as a place for photosynthesis and protein biosynthesis. Photosynthesis ability can be influenced by leaf morphology such as leaf color, leaf area and thickness, number of stomata and leaf shape. Pepper leaves have a variety of shapes that can be used as characteristics of a cultivar. The study aims to obtain information on nitrate reductase activity (NRA) from the leaf morphology of several pepper cultivars planted on peat land. The study was conducted using a non-factorial completely randomized design. The treatments consisted of Bengkayang pepper cultivar leaves divided into three leaf groups (wide, medium and narrow), Indian pepper cultivar leaves and 2 wild peppers in the form of Piper retrofractum and P. colonum. Samples were taken from community plantation, the third youngest leaf of 6 pepper stalks was selected. The results showed that in the Bengkayang pepper population there was a diversity of NRA values. Pepper with the highest ANR was shown in broad-leafed and Indian Bengkayang. The NRA values of broad-leaf, medium-leaf and small-leaf pepper were 5.92; 5.90; 5.81; and 5.78 µmol/hour/gr leaf weight, respectively. In the field, leaf area is an indicator of fast or slow growth rate. The leaf size of wild pepper Piper colonum and P. retrofractum ranges from medium to narrow and has better NRA compared to narrow-leaved Bengkayang